Evaluation of the morphometric relationships of a Calycophyllum spruceanum (Benth) Hook f. ex Schumann plantation at different spacings and depths - Chanchari Tello, Lizzanettsy Lizeth (2021)
Calycophyllum spruceanum (Capirona) is a timber species with high commercial value, however, there is limited information regarding morphometric relationships. Therefore, the objective of the present study was to evaluate the morphometric relationships of a C. spruceanum plantation at different distances and depths. The degree of slenderness, degree of coverage and index of living space were evaluated through a completely randomized block design (DBCA), with a factorial arrangement of 2 x 2, spacing of 3 mx 2 m and 3 mx 4 m, depth of 90 cm and 30 cm. No statistical differences were found between treatments. In the whole plantation, the values were admissible for each morphic degree. The degree of slenderness (0.68) showed a stable trend with respect to a higher density (3 x 2 m) and a lower depth (30 cm). The degree of coverage presented a higher proportion of crown (> 0.50). The living space index showed a tendency for the species to show higher growth.